Scaling of Fourier Spectra of strong earthquake ground motion in western Himalaya and northeastern India. Issue 102 (November 2017) - Gupta, I.D.; Trifunac, M.D.
Abstract: It is necessary to develop scaling models of various functionals of ground motions for different seismic regions to obtain region-specific motion characterizations for the design of structures and for seismic hazard studies. Until recently, a paucity of strong-motion data has limited such work in seismic regions in India. In this study, scaling of Fourier spectrum amplitudes is attempted for the western Himalayan and northeast regions of India in terms of magnitude, source-to-station distance, component orientation, and geological and soil site conditions. The scaling model considered is similar to that of Trifunac and co-workers for the California region in the 1980s and 1990s. A database of 1236 recorded accelerograms for both regions of India is used with the assumption that dependence on earthquake magnitude, site geology, site soil and component direction is the same. Separate attenuation models are then developed for the western Himalayan and northeast Indian regions in the period range of 0.03–3.0 s. The assumption of identical dependence of Fourier amplitudes on earthquake magnitude in the western Himalaya and northeast India region is found to be consistent with the actual data. These amplitudes grow with magnitude, reaching a maximum for magnitude around 7.0 for periods below 0.1 s and for magnitude exceeding 8.0 for longer periods. The Fourier amplitudes are amplified on sediments (with respect to basement rocks) at periods longer than 0.24 s, which are also amplified on "stiff soil" (with respect to the "rock" soil sites) at periods longer than 0.2 s. Extension of the proposed models to shorter and longer periods is also presented using the available techniques and validated by establishing their consistency with the independent estimates of seismic moment, stress drop, and radiated wave energy in both western Himalaya and northeast India. Highlights: Regionally dependent attenuation of strong motion from Himalayan earthquakes. Extension of strong motion Fourier Spectra in India to short and long periods. Scaling strong motion spectral amplitudes at distances up to 300 km. Tests of empirical Fourier Spectra in terms of seismic moment and energy.